Motivasi berprestasi pada mata pelajaran matematika siswa kelas x SMK Negeri Kebonagung - Elfita, Sari (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2024)
Achievement motivation is an encouragement and goal from the individual to achieve something that is intended as well as possible. In this study, the achievement motivation studied was in mathematics. This study aims to determine how high the achievement motivation of students in class X mathematics at Kebonagung State Vocational School. This research is a type of descriptive quantitative research. The population in this study was all of class X at Kebonagung State Vocational School, a sample of 100 students was taken using the simple random sampling method. The instrument in this study used an achievement motivation questionnaire which was taken directly. The data analysis was used a quantitative descriptive analysis with percentages. The results showed that achievement motivation in class X mathematics at Kebonagung State Vocational School had a percentage value in the very low category of 5%, the low category of 23%, the medium category of 44%, the high category of 19%, and the very high category 9%.